Effectiveness and safety of oral vancomycin for the treatment of inflammatory bowel disease associated with primary sclerosing cholangitis: a systematic review and pooled analysis - Wassel Sannaa; Mazen Almasry; Mustafa Peedikayil; Alyssa A. Grimshaw; Mashary Attamimi; Abdulelah AlMutairdi; Badr Al-Bawardy (Therapeutic Advances in Gastroenterology)
Background: Inflammatory bowel disease (IBD) occurs in up to 70%–80% of patients with primary sclerosing cholangitis (PSC). Oral vancomycin therapy (OVT) has been reported to be effective in the treatment of IBD associated with PSC (IBD-PSC). Objectives: To examine the effectiveness and safety of OVT in the treatment of IBD-PSC by performing a systematic review and pooled analysis of the literature. Design: We performed a systematic review and pooled analysis of studies reporting IBD clinical response to OVT in IBD-PSC. Data sources and methods: A systematic search was conducted in Cochrane Library, Embase, Google Scholar, Medline, PubMed, Scopus, and Web of Science from database inception to June 3, 2024. We included adult and pediatric studies that reported on clinical response (defined as any improvement in IBD-related clinical symptoms) of IBD-PSC patients treated with OVT (including pre- and post-liver transplantation cohorts). Pooled analyses of OVT response and safety were performed. Results: A total of 21 (open-label, non-controlled) studies including 290 patients with IBD-PSC treated with OVT were included. The median duration of OVT to treat IBD-PSC was 32.5 weeks (interquartile range (IQR): 19–83 weeks). The total daily dose of OVT ranged from 250 to 1500 mg. Concomitant treatment included the following: mesalamine in 14.5% ( n  = 42), advanced therapies in 10.7% ( n  = 31), and immunosuppressive agents in 14.1% ( n  = 41). Clinical response was noted in 47.6% (138/290) and clinical remission in 43.5% (100/230). The biochemical remission rate post-OVT was 68.8% (55/80) and endoscopic remission was 39.4% (80/203). Three studies ( n  = 11) reported no episodes of acute cholangitis while on OVT. Five studies ( n  = 69) reported an incidence rate of 8.7% of vancomycin-resistant enterococci post-OVT to treat IBD-PSC. Conclusion: OVT was associated with clinical response/remission in almost half of patients with IBD-PSC with a favorable side effect profile. Further prospective randomized trials are needed to confirm the dosing, efficacy, treatment duration, and long-term safety of OVT for the treatment of IBD-PSC. Trial registration: The study protocol was registered with PROSPERO a priori (no. CRD42023438341).